Exercise-Stress Echocardiography Reveals Systolic Anterior Motion of the Mitral Valve as a Cause of Syncopes in a Cardiac Amyloidosis Patient - Tor Skibsted Clemmensen; Henning Mølgaard; Niels Frost Andersen; Steen Baerentzen; Steen Hvitfeldt Poulsen (Case Reports in Cardiology)
Patients with cardiac amyloidosis are at increased AV-block and syncope risk. Therefore, a prophylactic pacemaker is often implanted. However, this case illustrates that other mechanisms should be ruled out prior to pacemaker implantation. The patient studied had mitral valve thickening without increased left ventricular outflow track (LVOT) velocity. However, bicycle exercise-stress test with simultaneous echocardiography revealed a stepwise decrease in blood pressure, a substantial increase in the LVOT velocity, and severe systolic anterior motion of the mitral valve. The patients’ symptoms were likely explained by these findings. Therefore, a comprehensive clinical evaluation is warranted prior to pacemaker implantation in cardiac amyloidosis patients.